Methods of estimation of the aerobic capacity development of the Chinese windsurfing team - Song, W.; Zheng, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Aerobic capacity is a necessary ingredient for the performance of sailing athletes. The principal duty of the Chinese national windsurfing team during winter-training in preparation for the 2008 Olympic Games was to develop aerobic capacity. This article examined the way of developing the aerobic capacity by monitoring the aerobic capacity of athletes. Methods The subject group consisted of 7 boys and 7 girls from the Chinese national windsurfing team were prescribed 40 minutes running and dynamometer during winter-training (from November 1st ,2007 to December 1st ,2007) in order to develop the aerobic capacity of athletes. The athletes` speed and power at anaerobic threshold was found when they ran and worked on a dynamometer after monitoring the five ranks of blood lactic acid in 2KM spot running and working on a dynamometer. The subjects then ran at that speed for 40 minutes and worked on the dynamometer. For each of the following weeks the speed and the work rate were increased regularly. After 4 weeks, the first step was repeated and the time of a 12 km run was recorded and used in the estimation of aerobic capacity. Results / Discussion Following completion of the training program the plot of blood lactic acid of athletes deviated to the right and the time of 12 km running after winter-training was lower than before winter training. The findings indicated 40 minutes running at anaerobic threshold and working on the dynamometer were effective ways to improve the aerobic capacity of athletes.